НЕМЕЦ ТИЛИ САБАҒЫНДА БАСЛАЎЫШ КЛАСС ОҚЫЎШЫЛАРЫНА ГРАММАТИКАНЫ ҮЙРЕТИЎДЕ ОЙЫНЛАРДЫҢ ӘҲМИЙЕТИ - Есбергенова, Г.Б. (ILIM hám JÁMIYET, 2025)
This article shows ways to increase the effectiveness of teaching in German language classes using pedagogical technologies, games in the classroom, the types of modern methods used in foreign language teaching methods and their use.